2021
DOI: 10.1002/agj2.20727
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen content of pea‐based cover crop mixtures and subsequent organic corn yield

Abstract: Organic growers rely heavily on manure additions to meet corn (Zea mays L.) nitrogen (N) needs. Considering the limited availability of farmyard manure and its increasing cost, the use of cover crop mixtures may help in addressing this challenge. The impact of fall-seeded cover crops with or without pelletized poultry manure application on corn yield and N dynamics was investigated at three sites in Québec, Canada. Cover crop treatments consisted of field pea (Pisum sativum L.) in a pure stand, 2-, 6-, and 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Additionally, the organic corn yields (8.6-11.6 Mg ha −1 ) observed in our study were higher than the organic corn grain yields (8.1-10.2 Mg ha −1 ) reported in a 3-year average study conducted by Champagne et al (2021) following the transition to certified organic land using hairy vetch + triticale or red clover + timothy at Pennsylvania State. While there is limited data available on legume-fed organic corn in Canada, a study by Lavergne et al (2021) demonstrated that legume cover crops (specifically pure pea as the primary nitrogen source) increased organic corn grain yield (5.6 Mg ha −1 ) compared to a no-cover crop control (4.0 Mg ha −1 ) in Québec, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the organic corn yields (8.6-11.6 Mg ha −1 ) observed in our study were higher than the organic corn grain yields (8.1-10.2 Mg ha −1 ) reported in a 3-year average study conducted by Champagne et al (2021) following the transition to certified organic land using hairy vetch + triticale or red clover + timothy at Pennsylvania State. While there is limited data available on legume-fed organic corn in Canada, a study by Lavergne et al (2021) demonstrated that legume cover crops (specifically pure pea as the primary nitrogen source) increased organic corn grain yield (5.6 Mg ha −1 ) compared to a no-cover crop control (4.0 Mg ha −1 ) in Québec, Canada.…”
Section: Discussionmentioning
confidence: 99%